Sturgeon Aquaculture - Specialized Techniques Determining the Stage of Sexual Maturity in Female Sturgeon for Artificial Spawning The Egg Maturation Assay - Frank A. Chapman; Joel P. Van Eenennaam (EDIS)
FA-154, a 4-page illustrated fact sheet by Frank A. Chapman and Joel P. Van Eenennaam, describes a biological test to determine if sturgeon eggs are in the stage of final maturation — the principle behind the test, materials needed, and protocol. Published by the UF Department of Fisheries and Aquatic Sciences, December 2007.